ADOPTING WEB-BASED LANGUAGE LEARNING (WBLL) AS LISTENING LEARNING RESOURCES: ESL-LAB FOR STUDENTS’ LISTENING IMPROVEMENT - Rani Aryanti Rukmana; Rini Fadhillah Putri (Universitas Negeri Medan, 2023)
The purpose of this present study was to investigate the learners' listening improvement and reactions when using ESL-Lab.com resources in English class. This study utilized the methodology of participatory action research, a methodical approach that is recognized for its ability to bring about change as a reaction to the difficulties faced by students during listening comprehension tasks. Â The present investigation was divided into three discrete phases: the pre-cycle, cycle 1, and cycle 2. The study was conducted to 30 participants at SMP Negeri 15 Medan, the PPL School while doing teaching practice from Pre-service Teacher Professional Education (PPG Prajabatan) program, from March to May 2023, in the eighth grader of the academic year 2022-2023. Data collection was done by test techniques and observation check list. The instruments used in this study were questionnaires and assessments. The results showed that there was an increase in the average score from preliminary score to achievement test cycle 1, from 49 to 64.67. The observed improvement amounted to an average of 15.67 points. Subsequently, following the execution of the second cycle, the second examination was administered, yielding an average score of 84.67. It is worth considering that the utilization of ESL-LAB resources might be advantageous in enhancing the foreign language listening skills of children in the developmental stage. Students (92.30%) perceive online platforms for learning foreign languages as engaging, while an overwhelming majority of respondents (96.15%) hold the belief that listening activities offered by ESL-LAB.com are effective.Â